1980
DOI: 10.1111/j.1432-1033.1980.tb04844.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the 14α‐Demethylation Mechanism in Cholesterol Biosynthesis

Abstract: Identification of radioactive 5a-cholest-8( 14)-ene-3p,7a-diol in extracts obtained from incubations of 3~-hydroxy-5a-[7-3H]cholest-7-ene-14a-carbaldehyde with rat liver microsomes is reported. Levels of this diol in incubations of the 1 4~-[ 3 2 -~ Hlcarbaldehyde were measured by multiple selected ion monitoring and were found to be of the same order of those of [3H]formate released from the substrate during the removal of the C-32 atom. The results demonstrate that the diol does not originate from known inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The similar phenomenon had been reported that cinnamaldehyde caused several genes involved in cell wall biosynthesis dysfunction 12,24 . Ergosterol is one of the principal sterol ingredients in the fungal membrane and is crucial for survival due to the ability in maintaining cell membrane fluidity, permeability, and pheromone signaling 4446 . In the present work, the transcriptional level of several genes related ergosterol was down-regulated, for example squalene monooxygenase Erg1 (AFLA_061500), C-14 sterol reductase (AFLA_051080 and AFLA_111350).…”
Section: Discussionmentioning
confidence: 99%
“…The similar phenomenon had been reported that cinnamaldehyde caused several genes involved in cell wall biosynthesis dysfunction 12,24 . Ergosterol is one of the principal sterol ingredients in the fungal membrane and is crucial for survival due to the ability in maintaining cell membrane fluidity, permeability, and pheromone signaling 4446 . In the present work, the transcriptional level of several genes related ergosterol was down-regulated, for example squalene monooxygenase Erg1 (AFLA_061500), C-14 sterol reductase (AFLA_051080 and AFLA_111350).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have demonstrated that hepatic microsomes can metabolize 14a-(hydroxymethyl)-5a-cholest-7-en-3/3-ol and 5a-cholest-8-ene-14a-carbaldehyde to demethylated products (Pascal, 1980;Galli-Kienle et al, 1980). Presumably this demethylation reaction is catalyzed by the lanosterol 14a-methyl demethylase.…”
Section: Discussionmentioning
confidence: 99%
“…5 ␣ -Cholestane and 19-hydroxycholesterol used as internal standards (IS) and BHT were purchased from Sigma Chemical Co. (St. Louis, MO). Deuterated lathosterol was synthesized (15). Silica cartridge columns (Supelclean…”
Section: Methodsmentioning
confidence: 99%